Understanding Christian Education According to the Synoptic Gospels and Its Implementation in Christian Education in the Church and Christian Families - Daulat Marulitua Tambunan (PT ARRUS Intelektual Indonesia, 2025)
Building a resilient generation in these end times requires full maturity . No adult hopes that their children will have a bleak future and a life full of evil. Parents' commitment to bring their children to God and educate them in the truth of God's Word consistently and continuously must be carried out. For this reason, it is necessary to understand Christian Education according to the Synoptic Gospels and its implementation in Christian Education in the church and family. The method in this study is a qualitative method that uses book sources as a reference to build theory and obtain good writing results. The results of this study are: according to the Synoptic Gospels, the implementation of Christian education in church services is: the ministry of preaching the word, liturgical service, fellowship service, diaconal service, witness service. Meanwhile, its implementation in the family is through intensive teaching and holding Bible studies in the family. Keywords: Christian Education, Synoptic Gospels , Church and Family.